Physical features, management and performance of Konkan cattle - SINGH, P K; PUNDIR, R K; DANGI, P S; DESAI, B G; BHAGAT, D J; KUMAR, SHALU (The Indian Journal of Animal Sciences, 2019)
The Konkan cattle are reared in all the districts of Konkan region of Maharashtra and Goa. In this study, phenotypic characterization of the Konkan cattle was carried out through systematic survey in its breeding tract and the breed descriptors were developed for its registration as a distinct breed. The population of Konkan cattle in the breeding tract is expected to be more than 6.0 lakhs. Konkan cattle are small to medium sized with compact body. The coat colours of Konkan cattle included Reddish dun, black, white, grey, brown or fawn or mixed, of which first two were in majority of animals. Biometry of 609 animals, which included 9 different body measurements in different age and sex groups, was recorded. When compared with Vechur and Malnad Gidda breeds of cattle of the coastal area of Kerala and Karnataka, the body weight and body measurements of Konkan cattle were found higher. The average horn length of Konkan cattle was 19.82 and 23.91 cm in cows and bullocks, respectively. The animals were kept in herd size varying from 2 to 20 with an average of 6.18 animals under extensive production system. The average age at first calving was 49.27 months with a calving interval of 17.21 months. It was observed that the average daily milk yield and peak milk yield of Konkan cattle were 2.23 and 3.28 kg. Animals of this breed are playing a significant role in the rural livelihood of farming community in terms of milk and bullocks power for agricultural operations in the hilly terrain of Konkan region. The unique physical features, biometry and their production system impart Konkan cattle population a distinct identity, therefore, it has been recently registered as a new cattle breed of India by Indian Council of Agricultural Research with accession number as INDIA_CATTLE_1135_KONKANKAPILA_03043 in the name of Konkan Kapila. Keeping in view the contribution of Konkan breed of cattle, State Animal Husbandry Department should come forward for further development and genetic improvement of the breed.